Micronutrients deficiencies and aluminum and manganese toxicity in cowpea - II - plant growth and chemical composition - Nogueira, Oscar Lameira; Paiva, José Braga; Crisóstomo, Lindbergue Araújo (Pesquisa Agropecuaria Brasileira, 2014)
In the present work the objectives were to study the effects of micronutrients boron copper, iron, manganese, molybdenum and zinc deficiencies, and aluminum and manganese toxicity on the growth (dry matter production) and chemical composition of cowpea plants ( Vigna unguiculata (L.) Walp. cv . Pitiúba). Treatment effects were statistically significant for dry weight of aerial part and roots of the plants. Nevertheless, the ratio aerial part/root was similar for all the treatments under study, Chemical analysis showed that the absence of an element resulted in the reduction of its concentration in the plant.
Keywords: dry matter; cowpea; Vigna unguiculata; cultivar